Electrical safety in low voltage distribution systems up to 1000 V a.c. and 1500 V d.c. Equipment for testing, measuring ormonitoring of protective measures. Resistance of earth connection and equipotential bonding Part 4, (15th July 1997) - British Standards Institution,
No abstract available